Application of electromagnetic navigation bronchoscopy-guided microwave ablation in multiple pulmonary nodules: a single-centre study. (7th February 2022) - Zeng, Chenxi; Fu, Xiangning; Yuan, Zhiwei; Hu, Shaojie; Wang, Xue; Ping, Wei; Cai, Yixin; Wang, Jianing
Abstract: OBJECTIVES: Electromagnetic navigation bronchoscopy (ENB)-guided microwave ablation is a minimally invasive technology for treating pulmonary lesions. This study analysed the short-term safety and efficacy of ENB-guided microwave ablation in multiple pulmonary nodules (MPNs). METHODS: This retrospective study reports a single-centre experience with ENB-guided microwave ablation for MPNs. Clinical, surgical and pathological data were obtained for patients who underwent ENB-guided microwave ablation from 23 December 2019 to 23 June 2021. The primary end points were technical safety and efficiency. RESULTS: The study assessed 65 patients who underwent ENB-guided microwave ablation, 57 of whom simultaneously underwent video-assisted thoracic surgery. In total, 216 nodules were treated. Of 96 nodules treated by ENB-guided microwave ablation, 94 nodules had ground-glass opacity. Ablation efficiency was confirmed by hybrid cone-beam computed tomography. Of 120 nodules surgically removed, 106 nodules had ground-glass opacity. The mean nodule size was 7.9 mm in ablated nodules and 10.2 mm in resected nodules. Distance between nodules and pleura or fissure was 17.45 mm in ablated nodules and 7.29 mm in resected nodules. The overall malignancy rate was 47.7% (103/216); the complication rate was low (65 patients). At short-term follow-up, the post-ablation target zone shrank by 1 week and stabilized after 4–6 months. No local recurrence or enlargement of other pulmonary nodules was noted. CONCLUSIONS: To treat MPNs, ENB-guided microwave ablation is safe and efficient. The combination of this treatment and video-assisted thoracic surgery is a potential application, which can preserve as much pulmonary function as possible and treat MPNs to the maximum extent. Abstract : Electromagnetic navigation bronchoscopy (ENB) is a minimally invasive technology to approach pulmonary lesions [1].